DON’T FORGET THE CALCIUM WHEN EVALUATING HYPOTONIA – CASE REPORT OF IDIOPATHIC INFANTILE HYPERCALCEMIA - Abazi Emini, Nora; Murtishi, Liridona; Ademi Shaqiri, Arba; Ismail, Ahmet; Isaku, Besmira; Gjorgjeski, Antonio; Izeti Kolonja, Mirzana; Puleska Risteska, Marina; Tasic, Velibor (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Idiopathic infantile hypercalcemia (IIH) is a rare genetic autosomal recessive disease characterized by hypercalcemia, hypercalciuria, and suppressed parathormone levels. It presents with a variety of clinical features, such as vomiting, dehydration, polyuria, lethargy, hypotonia, constipation, and poor weight gain. Renal ultrasonography demonstrates medullary nephrocalcinosis. The motive for hospitalization was lethargy, hypotonia, poor appetite, and poor weight gain. Biochemical findings revealed hypercalcemia, elevated vitamin D3 levels, suppressed intact parathormone levels, polyuria, hypercalciuria, and bilateral medullary nephrocalcinosis on renal ultrasound. The diagnosis was confirmed by sequence analysis of the coding exons of the gene CYP24A1 on the genomic DNA of the patient and identified two pathogenic variants of the gene [c.420_430 del];[c1147G>C].  Therapy with a short oral course of prednisolone, and dietary management with reduction of calcium and cessation of vitamin D intake had a satisfactory effect on the progress of body weight, improved motor skills, and normalized laboratory findings. In this case, we want to emphasize that when examining a child with hypotonia, we should always consider electrolyte disorders, in this case, hypercalcemia. Keywords: Idiopathic infantile hypercalcemia, CYP24A1, nephrocalcinosis, hypotonia.